Low-power inspection method for hot acid etching of super stainless steel and nickel-based corrosion-resistant alloys

By adding specific chemical substances and steam to the low-magnification inspection method of super stainless steel and nickel-based corrosion-resistant alloys, the problems of poor corrosion effect, long inspection cycle, poor safety and serious environmental pollution in the prior art are solved. It achieves fast, safe and environmentally friendly low-plus inspection results.

CN114910407BActive Publication Date: 2025-02-25SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210340875.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-02
Publication Date
2025-02-25
Estimated Expiration
2042-04-02

AI Technical Summary

Technical Problem

The existing low-power inspection methods have poor corrosion effects on solidification structure and defects of super stainless steel and nickel-based corrosion-resistant alloys, long inspection cycle, poor safety, and serious environmental pollution.

Method used

A new thermal acid corrosion low-magnitude inspection method is adopted. By adding ferric chloride, magnesium chloride, hydrochloric acid and sulfuric acid to the corrosion solution, and heating it with steam, the temperature is controlled at 75-85℃, and the heating is carried out for 30-40 minutes and gradually checked. The degree of corrosion of the sample ensures that solidified structure and defects are clearly displayed without corrosion.

Benefits of technology

It realizes a clear display of solidification structure and defects of super stainless steel and nickel-based corrosion-resistant alloys, shortens the inspection cycle to 60 minutes, improves inspection efficiency, ensures operational safety, reduces environmental pollution, and does not require equipment modification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114910407B_ABST
    Figure CN114910407B_ABST
Patent Text Reader

Abstract

The invention discloses a low-magnification inspection method for thermal acid etching of super stainless steel and nickel-based corrosion-resistant alloy, including: sample processing; placing the sample in a corrosion tank; adding a corrosive solution; passing steam for heating; continuing to heat and turning off the steam every 10-15 minutes to check the corrosion degree of the sample; taking out the sample after the corrosion is in place, using a brush to remove the corrosion products remaining on the inspection surface, and continuously rinsing with hot water, and finally drying with compressed air; the corrosive solution after inspection is discharged to a waste liquid treatment device, and discharged into the sewer after treatment; finally obtaining a clear solidification structure and a low-magnification inspection sample of defects. The invention can obtain the solidification structure of super stainless steel and nickel-based corrosion-resistant alloy without covering up defects, and the inspection result is very accurate; the inspection cycle is short; the operation is convenient and safe, and the environmental pollution is small; no modification or additional equipment is required; the advantage of steam heating that the corrosive solution can be stirred is fully utilized to ensure the uniformity of the corrosive solution, so that the sample is uniformly corroded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-magnification inspection method for the solidification structure and defects of super stainless steel and nickel-based corrosion-resistant alloy by thermal acid etching, and belongs to the field of low-magnification inspection of super stainless steel and nickel-based corrosion-resistant alloy. Background Art

[0002] At present, in order to achieve energy conservation and emission reduction, the production and application of high-performance, high-quality, long-life cycle and low-cost materials have become an important direction for the development of stainless steel and nickel-based corrosion-resistant alloys. In the face of modern industries in the process of industrialization in my country, such as petroleum, chemical, petrochemical, machinery, energy industry, environmental protection, marine development and other fields, large-scale equipment and key equipment, components, etc. have increased their demand for high corrosion resistance and high-quality super stainless steel and nickel-based corrosion-resistant alloy materials. For example, in order to meet the needs of stress corrosion, pitting and crevice corrosion and corrosion fatigue in harsh media in the development of modern industry, people have developed high-alloy super austenitic stainless steel with excellent pitting and crevice corrosion resistance, as well as nickel-based corrosion-resistant alloys with higher corrosion resistance. Among many inspection items such as mechanical property inspection, metallographic inspection, corrosion inspection, chemical composition inspection, etc., low-power inspection is often listed as the first in the order of inspection items.

[0003] There are many methods for low-magnification inspection, and there are many corrosion solutions and heating methods for hot acid etching low-magnification inspection according to different metals. In the actual production low-magnification inspection process of super stainless steel and nickel-based corrosion-resistant alloys, the low-magnification inspection methods in the current standards have some shortcomings and deficiencies, which are mainly reflected in the following four aspects:

[0004] 1. Poor corrosion effect. The corrosion liquid is uneven, the solidification structure is not clear, and the defects are covered.

[0005] 2. Long inspection cycle. Conventional hot acid etching method takes 6-36 hours to show solidified structure and defects, and the corrosion effect is poor.

[0006] 3. Poor safety. A large amount of toxic and harmful gases are produced during the corrosion process, and a large amount of foam is produced during the corrosion reaction, which poses a serious threat to human health and safety.

[0007] 4. Serious environmental pollution. The corrosion solution itself contains a variety of harmful substances, and it will react with the sample during the corrosion process to produce a large number of toxic and harmful compounds.

[0008] In order to obtain clear solidification structure and accurately display defects, shorten the inspection cycle, and use a low-magnification inspection method that is both safe and environmentally friendly, we have developed a new thermal etching low-magnification inspection method based on the thermal etching solution and equipment used in daily production inspection. Summary of the invention

[0009] The present invention aims to provide a low-magnification thermal acid etching inspection method for the solidification structure and defects of super stainless steel and nickel-based corrosion-resistant alloys, with the aim of solving the shortcomings and deficiencies of the current low-magnification inspection of the solidification structure and defects of super stainless steel and nickel-based corrosion-resistant alloys, such as poor corrosion effect, long inspection cycle, poor safety, and great environmental pollution.

[0010] The present invention is based on the perspective of solving the problems of the prior art. First, it should consider the solidification structure and the corrosion effect of defects. It can clearly display the solidification structure without covering up defects, so that the inspection results are accurate; second, it should shorten the inspection cycle and improve the inspection efficiency; third, it should ensure the safety of personnel during the operation and reduce the harm to the human body to the minimum; fourth, it should reduce the emission of toxic and harmful gases and waste liquids during the corrosion process. Another consideration is to take the existing equipment as the basis without major modifications and investments in the equipment.

[0011] The present invention provides a method for low-magnification thermal acid etching inspection of solidification structure and defects of super stainless steel and nickel-based corrosion-resistant alloy. The specific operation method is as follows:

[0012] (1) Sample processing: The test sample is cut to a thickness of 20mm-30mm. After precision turning or milling, ensure that the roughness of the test surface of the sample is no more than 0.1μm and there is no oil stain; the surface roughness requirement is high and can show solidification details and tiny defects.

[0013] (2) Place the sample in the corrosion tank. The samples must not come into contact with each other. If the corrosion tank is made of metal, the sample must not come into contact with the corrosion tank.

[0014] (3) Add 50-60g of ferric chloride, 10-15g of magnesium chloride, 1000-1200mL of water, 1000-1200mL of hydrochloric acid, and 100-110mL of sulfuric acid. The liquid level of the corrosion solution should be 60-70mm above the sample. 3+ Mg 2+ , H + , Cl - 、SO4 2- Under the joint action of H + It preferentially reacts electrochemically with impurity elements such as S and P that are segregated between crystals. 3+ Mg 2+ It acts as a corrosion inhibitor, which can clearly show the solidified structure and defects without causing excessive corrosion to cover up the structure and defects.

[0015] (4) Heat with steam and control the temperature at 75-85°C. After heating for 30-40 minutes, turn off the steam and check the corrosion degree of the sample. In order to accelerate the corrosion rate, add 500-600mL of hydrochloric acid to increase the H + The concentration accelerates intergranular corrosion and makes the solidification structure appear more clearly.

[0016] Steam heating can stir the corrosion solution, and the uniformity of the corrosion solution can be ensured during the corrosion process;

[0017] (5) Continue heating and turn off the steam every 10-15 minutes to check the corrosion degree of the sample until the solidification structure and defects of the sample are clearly shown, and prevent the false appearance of over-corrosion. The corrosion time generally does not exceed 60 minutes.

[0018] (6) After corrosion is complete, remove the sample, use a brush to remove the corrosion products remaining on the inspection surface, rinse it continuously with hot water, and finally blow it dry with compressed air.

[0019] (7) The corrosion solution after inspection cannot be reused and must be discharged into the waste liquid treatment device and then discharged into the sewer after treatment.

[0020] (8) Obtain a low-magnification inspection sample with clear solidification structure and defects. If there are special requirements, you can use image acquisition equipment to collect pictures. If you need to keep the sample, you can spray the sample with varnish to prevent rust.

[0021] Furthermore, the concentration of the hydrochloric acid is 36%, and the concentration of the sulfuric acid is 98%.

[0022] Beneficial effects of the present invention:

[0023] (1) It is possible to obtain the solidified structure of super stainless steel and nickel-based corrosion-resistant alloy without covering up defects, and the inspection results are very accurate.

[0024] (2) The inspection cycle is very short, and the inspection results can be obtained within 60 minutes.

[0025] (3) The operation is convenient and safe, with little environmental pollution, and is basically the same as the original hot acid etching operation.

[0026] (4) There is no need to modify or add equipment. The existing hot acid etching device can fully meet the requirements. It also makes full use of the advantage of steam heating to stir the etching solution. The uniformity of the etching solution can be ensured during the etching process, so that the sample can be corroded evenly. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 :N06625 Low magnification image of corrosion by common method;

[0028] Figure 2 : Low magnification image of the corrosion of N06625 of Example 1 by the method of the present invention;

[0029] Figure 3 : Low magnification image of the corrosion of N10276 of Example 2 by the method of the present invention;

[0030] Figure 4: Low magnification image of N06601 of Example 3 etched by the method of the present invention. DETAILED DESCRIPTION

[0031] The specific implementation manner of the present invention is described in detail below in conjunction with the embodiments, but the specific implementation manner of the present invention is not limited to the following embodiments.

[0032] The implementation steps are as follows:

[0033] Embodiment 1:

[0034] 1. Sample processing: Cut N06625 nickel-based corrosion-resistant alloy samples with a thickness of 25mm from the VIM+ESR ingot. After precision turning or milling, ensure that the roughness of the sample inspection surface is no more than 0.1μm and there is no oil stain.

[0035] 2. Place the N06625 sample into the corrosion tank. The samples must not come into contact with each other. If the corrosion tank is made of metal, the samples must not come into contact with the corrosion tank.

[0036] 3. Add 55g ferric chloride, 15g magnesium chloride, 1000mL water, 1100mL 36% hydrochloric acid, and 110mL 98% sulfuric acid. The liquid level of the corrosion solution should be 65mm above the sample.

[0037] 4. Heat with steam and control the temperature at 80°C. After heating for 35 minutes, turn off the steam and check the corrosion degree of the sample, and add 550mL of 36% hydrochloric acid again.

[0038] 5. Continue heating and turn off the steam every 10 minutes to check the corrosion degree of the sample until the solidification structure and defects of the N06625 sample are clearly shown. The corrosion time is 40 minutes.

[0039] 6. Take out the sample, use a brush to remove the corrosion products remaining on the inspection surface, rinse it continuously with hot water, and finally blow it dry with compressed air.

[0040] 7. The corrosion solution after inspection cannot be reused and should be discharged to the waste liquid treatment device and then discharged into the sewer after treatment.

[0041] 8. Obtain a clear low-magnification inspection sample of solidification structure and defects, see attached Figure 2 If there are special requirements, images can be collected using image acquisition equipment, and if samples need to be retained, they can be sprayed with varnish to prevent rust.

[0042] Embodiment 2:

[0043] 1. Sample processing: Cut N10276 nickel-based corrosion-resistant alloy samples with a thickness of 25mm from the VIM+VAR ingot. After precision turning or milling, ensure that the roughness of the sample inspection surface is no more than 0.1μm and there is no oil stain.

[0044] 2. Place the N10276 sample into the corrosion tank. The samples must not come into contact with each other. If the corrosion tank is made of metal, the samples must not come into contact with the corrosion tank.

[0045] 3. Add 60g ferric chloride, 15g magnesium chloride, 1000mL water, 1200mL 36% hydrochloric acid, and 120mL 98% sulfuric acid. The liquid level of the corrosion solution should be 70mm above the sample.

[0046] 4. Heat with steam and control the temperature at 85°C. After heating for 40 minutes, turn off the steam, check the corrosion degree of the sample, and add 600mL of new 36% hydrochloric acid.

[0047] 5. Continue heating and turn off the steam every 10 minutes to check the corrosion degree of the sample until the solidification structure and defects of the N10276 sample are clearly shown. The corrosion time is 60 minutes.

[0048] 6. Take out the sample, use a brush to remove the corrosion products remaining on the inspection surface, rinse it continuously with hot water, and finally blow it dry with compressed air.

[0049] 7. The corrosion solution after inspection cannot be reused and should be discharged to the waste liquid treatment device and then discharged into the sewer after treatment.

[0050] 8. Obtain a clear low-magnification inspection sample of solidification structure and defects, see attached Figure 3 If there are special requirements, images can be collected using image acquisition equipment, and if samples need to be retained, they can be sprayed with varnish to prevent rust.

[0051] Embodiment 3:

[0052] 1. Sample processing: Cut N06601 nickel-based corrosion-resistant alloy samples with a thickness of 25mm from the VIM+ESR ingot. After precision turning or milling, ensure that the roughness of the sample inspection surface is no more than 0.1μm and there is no oil stain.

[0053] 2. Place the N06601 sample into the corrosion tank. The samples must not come into contact with each other. If the corrosion tank is made of metal, the samples must not come into contact with each other.

[0054] 3. Add 50g ferric chloride, 10g magnesium chloride, 1000mL water, 1000mL 36% hydrochloric acid, and 100mL 98% sulfuric acid. The liquid level of the corrosion solution should be 60mm above the sample.

[0055] 4. Heat with steam and control the temperature at 75°C. After heating for 30 minutes, turn off the steam, check the corrosion degree of the sample, and add 500mL of new 36% hydrochloric acid.

[0056] 5. Continue heating and turn off the steam every 10 minutes to check the corrosion degree of the sample until the solidification structure and defects of the N06601 sample are clearly shown. The corrosion time is 30 minutes.

[0057] 6. Take out the sample, use a brush to remove the corrosion products remaining on the inspection surface, rinse it continuously with hot water, and finally blow it dry with compressed air.

[0058] 7. The corrosion solution after inspection cannot be reused and should be discharged to the waste liquid treatment device and then discharged into the sewer after treatment.

[0059] 8. Obtain a clear low-magnification inspection sample of solidification structure and defects, see attached Figure 4 If there are special requirements, images can be collected using image acquisition equipment, and if samples need to be retained, they can be sprayed with varnish to prevent rust.

Claims

1. A low-magnification test method for hot acid etching of super stainless steel and nickel-based corrosion-resistant alloy, characterized in that The following steps are involved: (1) Sample processing: Cut the test sample with a thickness of 20mm-30mm, and ensure that the roughness of the test surface of the sample is no more than 0.1μm after fine turning or fine milling, and there is no oil stain; (2) Place the sample in the corrosion tank. The samples must not come into contact with each other. If the corrosion tank is made of metal, the sample must not come into contact with the corrosion tank. (3) Add the etching solution: 50-60g of ferric chloride, 10-15g of magnesium chloride, 1000-1200mL of water, 1000-1200mL of hydrochloric acid, and 100-110mL of sulfuric acid. The liquid level of the etching solution is required to be 60-70mm above the sample. The hydrochloric acid is 36% in concentration, and the sulfuric acid is 98% in concentration. (4) Heat with steam. After heating for 30-40 minutes, turn off the steam and check the corrosion degree of the sample. In order to accelerate the corrosion rate, add 500-600mL of hydrochloric acid to increase the H + The concentration of the hydrochloric acid is 36%, which accelerates the corrosion between the crystals and makes the solidification structure appear more clearly. (5) Continue heating and turn off the steam to check the corrosion degree of the sample every 10-15 minutes until the solidification structure and defects of the sample are clearly shown; (6) After the corrosion is complete, take out the sample, use a brush to remove the corrosion products remaining on the inspection surface, rinse it continuously with hot water, and finally blow it dry with compressed air; (7) The corrosion solution after inspection is discharged to the waste liquid treatment device and then discharged into the sewer after treatment; (8) Obtain low-magnification inspection specimens with clear solidification structure and defects.

2. The low-magnification thermal acid corrosion inspection method for super stainless steel and nickel-based corrosion-resistant alloy according to claim 1, characterized in that: In step (4), the temperature of the steam is controlled at 75-85°C.

3. The low-magnification thermal acid etching inspection method for super stainless steel and nickel-based corrosion-resistant alloy according to claim 1 is characterized in that: In step (5), the etching time does not exceed 60 minutes.

Citation Information

Patent Citations

  • Chemical etching liquid and method for displaying raw stainless steel austenite grain boundary

    CN103698192A

  • Nickel based corrosion-resisting alloy dendritic crystal etching agent and preparation method and using method thereof

    CN104634640A